PENGUKURAN BEBAN KERJA DENGAN METODE FISIOLOGI (STUDI KASUS PADA “X” FITNESS CENTER AMBON) - Novita Irma Diana Magrib (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2018)
Services provided by the “X” fitness center fitness facility with a variety of tools already available, the “X” fitness center, most customers are men, where most of the activities carried out are activities of lifting barbells of various sizes. From this it will be calculated the amount of energy consumption based on heart rate and recommend the lifting load limit corresponding to anthropometrics Indonesian workers.Based on the calculation of loading equation then the average energy required for lifting the load 12 Kg, 16 kg, and 20 Kg were 3-6 kilocalories / minute. Thus removal of the load on the “X” Fitness Center with a size of 12 kg, 16 kg and 20 kg was allowed for the appointment, because the load with so many sizes still categorized in mild and moderate workloads